Surgical Antimicrobial Prophylaxis in Neonates and Children Undergoing Neurosurgery: A RAND/UCLA Appropriateness Method Consensus Study - Susanna Esposito; Mino Zucchelli; Sonia Bianchini; Laura Nicoletti; Sara Monaco; Erika Rigotti; Laura Venditto; Cinzia Auriti; Caterina Caminiti; Elio Castagnola; Giorgio Conti; Maia De Luca; et al. (Antibiotics, 2022)
Pediatric neurosurgery is a highly specialized branch of surgery in which surgical site infections (SSIs) are potentially serious complications that can also adversely affect a good surgical outcome, compromising functional recovery and, in some cases, even putting the patient’s life at risk. The main aim of this consensus document is to provide clinicians with a series of recommendations on antimicrobial prophylaxis for neonates and children undergoing neurosurgery. The following scenarios were considered: (1) craniotomy or cranial/cranio-facial approach to craniosynostosis; (2) neurosurgery with a trans-nasal-trans-sphenoidal approach; (3) non-penetrating head injuries; (4) penetrating head fracture; (5) spinal surgery (extradural and intradural); (6) shunt surgery or neuroendoscopy; (7) neuroendovascular procedures. Patients undergoing neurosurgery often undergo peri-operative antibiotic prophylaxis, with different schedules, not always supported by scientific evidence. This consensus provides clear and shared indications, based on the most updated literature. This work has been made possible by the multidisciplinary contribution of experts belonging to the most important Italian scientific societies, and represents, in our opinion, the most complete and up-to-date collection of recommendations on the behavior to be held in the peri-operative setting in this type of intervention, in order to guide physicians in the management of the patient, standardize approaches and avoid abuse and misuse of antibiotics.